2021
DOI: 10.1101/2021.02.14.431096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying and Mitigating Motor Phenotypes Induced by Antisense Oligonucleotides in the Central Nervous System

Abstract: Antisense oligonucleotides (ASOs) are emerging as a promising class of therapeutics for neurological diseases. When injected directly into the cerebrospinal fluid, ASOs distribute broadly across brain regions and exert long-lasting therapeutic effects. However, many phosphorothioate (PS)-modified gapmer ASOs show transient motor phenotypes when injected into the cerebrospinal fluid, ranging from reduced motor activity to ataxia or acute seizure-like phenotypes. The effect of sugar and phosphate modifications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…Further, combinatorial treatment with NBQX potentiated decreases in intracellular free calcium levels induced by ASO2 ( Figure 6 A) and modified ASO5 ( Figure S10 ) previously reported to be neurotoxic ( Table S1 ). 22 Then, we confirmed the maximum tolerated dose, i.e., 13.1 nmol, at which NBQX itself did not induce neurotoxicity according to scoring with the ATSS ( Figure S11 A) and open-field tests ( Figure S12 ). Acute tolerability scores in mice injected with ASO1 after pretreatment with the tolerated dose of NBQX were higher than those of mice injected with ASO1 after pretreatment with PBS as a negative control (the total acute tolerability score of the NBQX and PBS group at 1 h were 6.8 and 4.8, respectively; Figure 6 B; Video S2 ).…”
Section: Resultssupporting
confidence: 54%
“…Further, combinatorial treatment with NBQX potentiated decreases in intracellular free calcium levels induced by ASO2 ( Figure 6 A) and modified ASO5 ( Figure S10 ) previously reported to be neurotoxic ( Table S1 ). 22 Then, we confirmed the maximum tolerated dose, i.e., 13.1 nmol, at which NBQX itself did not induce neurotoxicity according to scoring with the ATSS ( Figure S11 A) and open-field tests ( Figure S12 ). Acute tolerability scores in mice injected with ASO1 after pretreatment with the tolerated dose of NBQX were higher than those of mice injected with ASO1 after pretreatment with PBS as a negative control (the total acute tolerability score of the NBQX and PBS group at 1 h were 6.8 and 4.8, respectively; Figure 6 B; Video S2 ).…”
Section: Resultssupporting
confidence: 54%
“…Interestingly, at this second site, we observed that the steric blocker ASOs S30-6, S30-4, S30-2 and S30 induced a similar level of FXN activation to their gapmer ASOs, demonstrating that RNA cleavage was not required for FXN activation (Figure 2F ). Our previous work showed that gapmer ASOs might trigger more severe neurotoxicity in mouse brain than steric blocker ASOs targeting the same sequence ( 26 ). Thus, in moving forward, we focused our work on the steric blocker S30 at this region.…”
Section: Resultsmentioning
confidence: 99%
“…Unilateral intracerebroventricular (ICV) injections were carried out under UMass Chan Medical School IACUC protocol A-2551 as previously described ( 26 ). In brief, YG8R mice at ∼12 weeks old were anesthetized by intraperitoneal injection of a sterile saline solution containing fentanyl/midazolam/dexmedetomidine (0.1, 5 and 0.25 mg/kg, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…As a pilot behavioral study, we performed an intrathecal injection of ASO5-2 at 2 mg kg −1 in four sheep. For intrathecal injection in sheep, it was necessary to thread a microcatheter up though the intrathecal space and deliver the ASO directly into the cisterna magna (Methods) 34 . Intracisternal contrast injection and cone beam computed tomography confirmed the correct catheter position before ASO injection.…”
Section: Sustained Potency Of Mixed Backbone Aso5-2 In Two Mouse Modelsmentioning
confidence: 99%
“…Both of these analogues showed reduced motor phenotypes and a higher MTD than ASO5. Elsewhere, we explore the mechanism of the motor phenotypes observed here and follow-up on the improvement observed by mixed backbone modification patterns 34 .…”
mentioning
confidence: 90%